Hubungan Antara Forward Head Posture dengan Keseimbangan Dinamis - Tawakkalni, Audiyah; , Sugiono, S.Fis.MH.Kes (2017)
RELATIONSHIP BETWEEN THE FORWARD HEAD POSTURES WITH DYNAMIC BALANCE S1 Physyotherapy Study Program Health Faculty Muhammadiyah University Surakarta Email: audi.tawakkalni@gmail.com Abstract Background: The position of the body when using electronic media usually flexi the neck to stare at lower object and keep the head in position in front for long periods of time. With the body posture, head posture decline in cervical lordosis of the lower cervical vertebrae and create a curve in the upper posterior thoracic vertebrae to maintain the balance, this is known as forward head posture. The neck posture will change the center of gravity (COG) that would disrupt the balance. The balance is defined as the body's ability to maintain the body's center of mass to the plane of the pivot. The balance is a complex integration of sensory and musculoskeletal systems are regulated in the brain in response to internal and external changes in the body. Purpose: Knowing the relationship between forward head posture with dynamic balance. Methods: The study was observational with cross sectional approach. The sampling technique used purposive sampling, is sampling based on certain criteria, with a total sample of 50 respondents. Results were analyzed by using the Pearson product moment correlation test.. Results: Analysis of data by using the Pearson product moment correlation test that shows the results p = 0.001 (p <0.05), then Ho is rejected and Ha accepted. Conclusions: There is a relationship between forward head posture with dynamic balance. Keywords: Forward Head Posture, Dynamic Balance, Star Excursion Balance Test.